Breast cancer screening: a narrative review - Kaundal, Asmita; Bhavna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Breast cancer (BC) is the most commonly diagnosed cancer and a leading cause of cancer-related mortality among women worldwide, accounting for over 2.5 million cases and 670,000 deaths annually. The burden is disproportionately higher in low- and middle-income countries (LMICs) due to limited access to screening, poor infrastructure, low awareness, and socio-cultural barriers. Early detection through screening plays a critical role in improving survival and reducing morbidity. This review outlines the epidemiology of breast cancer (BC), stratification of risk, and current international and national screening guidelines. Various screening modalities are discussed, including mammography, ultrasound, MRI, clinical breast examination (CBE), and emerging technologies such as artificial intelligence and liquid biopsy. The role of innovative tools such as the iBreastExam and, community-based strategies in resource-limited settings is emphasized. Despite advances, key challenges remain regarding accessibility, affordability, and awareness.